PENGARUH TATA KELOLA PERUSAHAAN DAN KONEKSI POLITIK TERHADAP PENGHINDARAN PAJAK - Asti Alifa Muazaroh (2022)
This study aims to determine the effect of corporate governance and political connection on tax avoidance. Measurement of tax avoidance using Book Tax Difference (BTD). This study uses a sample of 155 samples by focusing on mining companies listed on the Indonesia Stock Exchange in 2016-2020. The analytical technique used is multiple linear regression analysis with panel data regression using the STATA application program and 5% as the level of significance used in this study. The results of this study show that (1) the proportion of independent commissioners has no effect on tax avoidance, (2) the audit committee has no effect on tax avoidance, (3) managerial ownership has no effect on tax avoidance, and (4) political connections have no effect on tax avoidance.